1-Benzyl-2,5-dioxopyrrolidine-3,4-diyl diacetate - Caracelli, I.; Ferreira, F.P.; Vieira, A.S.; Stefani, H.A.; De Simone, C.A.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The pyrrolidine-2,5-dione ring in the title compound, C15H15NO6, is in a twisted conformation with the acetyl C atoms projecting to opposite sides of the ring. The acetyl groups lie to opposite sides of the five-membered ring. The benzene ring is roughly perpendicular to the heterocyclic ring, forming a dihedral angle of 76.57 (14)degrees with it. In the crystal, molecules are connected through a network of C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions.